2008
DOI: 10.1002/rcm.3858
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of equine urine reactivity towards phase II metabolites of 17‐hydroxy steroids by liquid chromatography/tandem mass spectrometry

Abstract: Proper storage conditions of biological samples are fundamental to avoid microbiological contamination that can cause chemical modifications of the target analytes. A simple liquid chromatography/tandem mass spectrometry (LC/MS/MS) method through direct injection of diluted samples, without prior extraction, was used to evaluate the stability of phase II metabolites of boldenone and testosterone (glucuronides and sulphates) in intentionally poorly stored equine urine samples. We also considered the stability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…In previous studies, boldienone (androsta-1,4-diene-3,17-dione) and its isotope-labelled analogues were formed in a small number of the inappropriately stored equine urine samples (room temperature) that had been spiked either with testosterone (17β-hydroxyandrost-4-en-3-one) glucuronide or isotope-labelled analogues of testosterone and androstenedione (androsta-4-diene-3,17-dione). 7,8 Furthermore, storage at room temperature resulted in the formation of isotopelabelled analogues of boldenone and Δ1-progesterone (pregn-1,-4-diene-3,20-dione) from isotope-labelled analogues of testosterone and progesterone (pregn-4-ene-3,20-dione), respectively, in spiked equine urine samples. 8 Inadvertent exposure of a urine sample to faeces may also introduce microbes in the sample and lead to the detection of boldenone, as demonstrated in human urine 9 and bovine faeces.…”
mentioning
confidence: 99%
“…In previous studies, boldienone (androsta-1,4-diene-3,17-dione) and its isotope-labelled analogues were formed in a small number of the inappropriately stored equine urine samples (room temperature) that had been spiked either with testosterone (17β-hydroxyandrost-4-en-3-one) glucuronide or isotope-labelled analogues of testosterone and androstenedione (androsta-4-diene-3,17-dione). 7,8 Furthermore, storage at room temperature resulted in the formation of isotopelabelled analogues of boldenone and Δ1-progesterone (pregn-1,-4-diene-3,20-dione) from isotope-labelled analogues of testosterone and progesterone (pregn-4-ene-3,20-dione), respectively, in spiked equine urine samples. 8 Inadvertent exposure of a urine sample to faeces may also introduce microbes in the sample and lead to the detection of boldenone, as demonstrated in human urine 9 and bovine faeces.…”
mentioning
confidence: 99%
“…4 In addition, fungal species in corn have been reported to convert androstenedione to boldione and then further to boldenone. For example, Fidani et al 10 showed that boldione was detected in 10% of inappropriately stored equine urine samples spiked with testosterone glucuronide. 6 It has also been reported that black oats, contaminated with fungus and insects, contained boldenone and boldione, and its ingestion resulted in the excretion of boldenone sulfate in equine urine.…”
mentioning
confidence: 99%
“…It is theorized that boldenone could be formed in equine urine in particular where postcollection storage conditions are unfavorable (temperature/extended period). For example, Fidani et al 10 showed that boldione was detected in 10% of inappropriately stored equine urine samples spiked with testosterone glucuronide. Additionally, inadvertent exposure of a urine sample to feces may result in the formation of boldenone, as demonstrated in both human urine 11 and in bovine feces.…”
mentioning
confidence: 99%
“…This unexpected increase might result from possible conversion of testosterone glucuronide present in urine [27] to androstenedione [28]. Testosterone concentration in all the urine samples was close to LOQ and did not noticeably change with storage time (data not shown).…”
Section: Results From Fresh Plasma and Urine Samplesmentioning
confidence: 66%